A rare case of iatrogenic vesicovaginal fistula arising from a forgotten gauze strip during Caesarean section - Boyan Stoykov; Nikolay Kolev; Vladislav Dunev; Pencho Genov (Urology Case Reports, 2020)
The incidence of iatrogenic vesicovaginal fistulas in women after gynecological surgery is 82%, as hysterectomy being the most common cause for them - 88%. We presented a rare case of iatrogenic vesicovaginal fistula resulting from a series of errors and forgotten gauze strip in a 26-years-old woman after a third Caesarean section. Keywords: Iatrogenic vesicovaginal fistula, Forgotten gauze strip